Spor glede vezanosti na referendumsko odločitev - Kaučič, Igor (Podjetje in delo, 2018)
After the 2013 constitutional amendment, which removed the provision on the binding nature of the voters' decision in a legislative referendum for the National Assembly from Article 90, this constitutional rule only remains valid for the referendum on international associations. On a legislative level, this question is regulated for other state and local referendums; however, the rule differs not only by its constitutional basis, but also by substance and extent. The regulation of the question in relation to legislative referendum is especially out-standing. Since the Referendum and Popular Initiative Act still, after five years, has not been modified in line with the constitutional amendment, the question of the constitutionality of the law's provisions on a one-year prohibition on adoption of a law in contradiction with the voters' decision, and potential following conflicts, arises. Only the Constitution can bind the legislator; therefore, it is questionable from a constitutional law point of view if a legislative act may stipulate how and for how long the outcome of a referendum should bind the National Assembly. Such a provision importantly limits the National Assembly in performing its fundamental constitutionally determined legislative function. If the one-year suspensive deadline is retained, a law passed in contradiction with the prohibition could be subject to a formal (procedural) constitutional review by the Constitutional Court. Regardless of the rules on the binding nature of the decision, it has to be taken into account that the National Assembly is not bound by the decision if it would give rise to an unconstitutional situation. In such cases, it has to eliminate the unconstitutionality of the law, as determined by the Constitutional Court, regardless of the voters' referendum decision.
Keywords: formalna protiustavnost zakona; prepoved sprejetja zakona; referendumska odločitev; suspenzivni rok; ustavnosodna presoja referenduma; vezanost Državnega zbora; zakonodajni referendumi